Consumption in Asset Returns - BRYZGALOVA, SVETLANA; HUANG, JIANTAO; JULLIARD, CHRISTIAN (Journal of Finance, 2026)
ABSTRACT Using information in returns, we identify the stochastic process of consumption. We find that aggregate consumption reacts over multiple quarters to innovations spanned by financial markets. This persistent component accounts for over a quarter of consumption variation. These shocks command a large and significant risk premium, driving a large share of stocks' and a small yet significant fraction of bonds' time‐series variation. Nevertheless, we find no support for stochastic volatility of consumption driving time‐varying risk premia. Finally, an otherwise standard recursive utility model based on our estimated process explains equity premium and risk‐free rate puzzles with low‐risk aversion.